The scandal of evangelism: a biblical study of the ethics of evangelism - Thiessen, Elmer John (Wipf and Stock Publishers, 2018)
Intro -- Title Page -- Acknowledgments -- Chapter 1: Introduction -- Chapter 2: An Approach to Biblical Ethics and the Ethics of Evangelism -- Part I: Ethics of Evangelism in the New Testament -- Chapter 3: The Gospels and Jesus -- Chapter 4: Acts and the Apostles -- Chapter 5: Paul's Epistles -- Chapter 6: General Epistles and Revelation -- Chapter 7: Summary of Biblical Analysis: Guidelines for Ethical Evangelism -- Part II: Applied Topics -- Chapter 8: Evangelism of Children -- Chapter 9: Evangelism in Professional Life: The Academy -- Chapter 10: Evangelism and Humanitarian Aid -- Chapter 11: Ethics of Proselytism -- Chapter 12: Conclusion -- Bibliography.